THE IMPORTANCE OF THE APPLICATION OF PSYCHOMORICITY IN THE EARLY YEARS OF ELEMENTARY SCHOOL FOR THE COGNITIVE DEVELOPMENT OF STUDENTS - Barros, Izabel Maria de; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The present articleaims to demonstrate the importance of psychomotricity in the early years of elementary school and how it contributes positively to the cognitive development of the child. Through games, games and playful activities that a motor and psychoemotional development. The professionals have to be able to perform them so that the benefits are directed to the students.